1971
DOI: 10.1172/jci106509
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate inhibition of sodium reabsorption in the unilaterally diseased kidney of dog and man after an acute saline load

Abstract: A B S T R A C T Clearance studies were performed on 49 split-bladder dogs with a unilateral pyelonephritic or remnant kidney and three patients with unilateral kidney disease to examine the effects of an acute saline load on the diseased kidney (DK) as opposed to a simultaneously studied, contralateral control kidney (CK), which also served to maintain a nonuremic environment.Before saline loading, base line studies in many of the dogs and the three humans were in agreement with previously published data. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
1

Year Published

1973
1973
1984
1984

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
4
11
1
Order By: Relevance
“…In addition, maximum tubular secretion of PAH per GFR was similar for both the APGN and intact kidney, also in contrast to the group I studies. These results for the group II studies are similar to those reported for the unilateral pyelonephritic and chronic glomerulonephritic dog models (10,11,15,16 It is interesting to note that in dog 75, despite a stable GFR in the diseased kidney, the sodium excretory pattern changed as the disease became chronic.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In addition, maximum tubular secretion of PAH per GFR was similar for both the APGN and intact kidney, also in contrast to the group I studies. These results for the group II studies are similar to those reported for the unilateral pyelonephritic and chronic glomerulonephritic dog models (10,11,15,16 It is interesting to note that in dog 75, despite a stable GFR in the diseased kidney, the sodium excretory pattern changed as the disease became chronic.…”
Section: Discussionsupporting
confidence: 82%
“…Sodium handling by the intact kidney in both models I and II was similar to the intact kidney in the dog model with a unilateral remnant or pyelonephritic kidney (11). Thus, it seems unlikely that a circulating antinatriuretic substance was responsible for decreased sodium excretion by the APGN kidney in group I.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Although altered renal transport of sodium in chronic renal failure is well known and has been the subject of intensive investgation (1)(2)(3)(4)(5)(6)(7)(8)(9)(17)(18)(19), the manner by wnvhich this change in renal handling of sodium takes place at various sites of the nephron has not been elucidated. Micropuncture studies performed in the past using various experimental models have centered mostly on the transport changes in the proximal tubule (5)(6)(7)(8) and rarely in the distal segments (9).…”
Section: Discussionmentioning
confidence: 99%